ASSESSMENT OF THE INDIGENOUS KNOWLEDGE OF FARMERS ON POST-HARVEST STORAGE OF TOMATO IN JIGAWA STATE, NIGERIA - Bello, O. G.; Halidu, J.; Aliyu, A. S.; Koloche, I. M.; Popoola, O. P.; Gbadamosi, F. Y. (FUDMA JOURNAL OF SCIENCES, 2023)
The study assessed farmers’ indigenous knowledge on post-harvest handling/storage of tomato in Jigawa State, Nigeria. One hundred and twenty (120) respondents were randomly selected for the study. Most of the respondents were males (90.0%), Muslims (95.9%), married (89.2%), with average age of 34 years, average household size of 9 persons and farm size of 4.2ha. Average monthly income and farming experience were N26, 075.00 and 13 years. About 40% had no formal education (40.0%) while only 10.0% had primary, secondary or tertiary education respectively and most (84.2%) of the respondents had no extension contact. The highly practiced indigenous knowledge on tomato post-harvest handling/storage were; selective picking (M=1.017), dry within homestead (M=1.050) and spreading on sand free surface for drying (M=1.067) among others. Major constraints to post-harvest storage are; inadequate capital, government policies, inadequate infrastructures (M=3.78) and lack of equipments (M=3.70) and lack of current technologies on postharvest storage (M=3.67). The Chi-square analysis shows significance between farming experience and household size with the indigenous knowledge on post-harvest storage of tomato. It was recommended that government should incorporate policies that would be focused on post-harvest storage to reduce wastage of the product in the national policy document, improved and adoptable technologies that are simple, cheap and compactable with the socio-cultural background of the farmers must be in place and extension should be employed to provide up to date technologies on post-harvest handling/storage of tomato to the respondents.